Қазақ тілі сабақтарында сын тұрғысынан ойлау технологиясының элементтерін пайдалана отырып, оқушының тілдік құзыреттіліктерін дамыту - Шалдыбаева, Б.Т. (My University, 2016)
This article presents the experience of the work of the teacher with the theoretical and practical basis for the use of critical thinking. These bases allow students to develop skills needed in the 21 st century, such as communication skills, creativity, analytical thinking, the development of language skills that are facilitated cooperation- the teacher guides, advises and monitors while students independently plan, do, analyze and evaluate themselves. Within the framework of the article suitable methods and techniques of teaching the Kazakh language are revealed. The main objectives of the article suggest: -to identify peculiarities, goals, objectives and techniques of TDCT as the technology of general pedagogy; -to explain the importance of critical thinking; -to substantiate the possibility and the need of the use of TDCT in the process of teaching; -to present the methods of TDCT used in the lessons. Thus, the object of the research of the article is the process of teaching the Kazakh language and the subject is the use of TDCT in the lessons of the Kazakh language
Keywords: critical thinking; development; personality; linguistic competence; teacher; student; method